Moolang: Cultural Representation and Education Spaces in Malang Raya - Yogi Dwi Satrio; Vidya Purnamasari; Yon Ade Lose Hermanto; Ni'matul Istiqomah; Vika Annisa Qurrata; Rizza Megasari (International Journal of Community Service Learning, 2026)
This community service initiative stemmed from the lack of educational platforms that instill the cultural value of cooperation. Therefore, the goal of this activity was to strengthen local culture-based education, which is crucial for facing the Society 5.0 era, through the Moolang application. This application integrates cultural values , such as cooperation, into digital learning. This activity involved a community of economics teachers from across Malang and 50 students using an outcome-based approach. This activity was carried out in three stages: socialization, implementation, and evaluation. During the socialization phase, teachers received training on using the Moolang application, while the implementation phase integrated it into school economics learning activities. The evaluation was conducted through a questionnaire that showed positive results, indicating that Moolang improved students' understanding of cultural values and collaboration skills. Descriptive analysis showed high satisfaction with the application's navigation and content, although there were complaints about bugs and suboptimal audio-visual quality. Most teachers stated that they would recommend this application to their colleagues. In conclusion, virtual educational spaces play a crucial role in representing local culture and shaping students' identities by integrating cultural values, symbols, and practices into the digital learning process. The implication is that the development of virtual learning should consciously integrate local cultural elements to strengthen students' cultural identity and increase the relevance of learning in the digital era.